Selection response for feed conversion and growth traits in polled Hereford cattle - Glaze, J.B. Jr.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Direct and correlated responses to selection for improved feed conversion were estimated from performance records of 1459 Polled Hereford cattle born from the spring of 1967 through the spring of 1979. Data were analyzed using a multiple-trait, derivative-free, restricted maximum likelihood (MTDFREML) procedure. A full animal model was used to calculate genetic and phenotypic (co)variances. The withinherd breeding values that resulted from the solution of the mixed model equations were regressed on year to create selection response curves. Feed conversion was shown to respond favorably to direct selection, with feed/gain changing -.005 per year.
Keywords: Beef; Selection; Response; Feed conversion; Polled Hereford